EFEKTIVITAS TEKNIK PARADOXICAL INTENTION UNTUK MEREDUKSI KECEMASAN KOMUNIKASI PESERTA DIDIK PADA PROSES PEMBELAJARAN DI KELAS - Frans Dwi Oktareza, - (2018)
Penelitianditujukanuntukmengujikeefektifankonselingparadoxical intentionuntukmereduksikecemasankomunikasipesertadidik.Penelitianinimenggunakanpendekatankuantitatifdenganmetodekuasieksperimendengandandesainpenelitiannonequivalent control group design.Teknikpengumpulan data dilakukanmenggunakaninstrumenkecemasankomunikasipesertadidik.Sampelpenelitianyaitupesertadidikkelas X SMA N 1 PedamaranTahunajaran 2017/2018 yang memilikitingkatkecemasankomunikasi yang sangattinggi.Teknikanalisis data menggunakanuji t. Hasilpenelitianmenunjukkanbahwaterdapatlimakatagoritingkatankecemasankomunikasi, yaitu: sangattinggi, tinggi, sedang, rendahdansangatrendah. Perlakuanpadakatagorisangattinggidifokuskanuntukterjadinyareduksimenujukatagorirendah.Hasilpenelitianmenunjukkanbahwateknikparadoxical intention efektifuntukmereduksikecemasankomunikasipesertadidik.Konselordiharapkanmampumenerapkankonselingparadoxical intentionuntukmereduksikecemasankomunikasiterhadappesertadidik. ;---The study aimed to test the effectiveness of paradoxical intention counseling to reduce the studentscommunication apprehension. This study uses a quantitative approach. The research method used is quasi experiment with research design nonequivalent control group design. Data collection techniques were conducted using instrument of communication apprehension. The sample of research is the students of class X SMA N 1 Pedamaranin year 2017/2018 which has a very high level of communication apprehension. Data analysis technique using t-test. The results showed that there are five categories of communication apprehension level, namely: very high, high, medium, low and very low. Treatment in very high category focused on the occurrence of reduction to low category. The results showed that paradoxical intention technique is effective for reducing the communication apprehension of learners. Counselors are expected to be able to apply paradoxical intention counseling to reduce coomunication apprehension to learners.